2018
DOI: 10.3390/ijerph15122810
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Applications for Mindfulness Interventions with Suicidality in Asian Older Adults: A Literature Review

Abstract: Elderly suicide is a rising concern. Despite the advent of mobile technology, there remained a gap in the evidence base as to whether smartphone applications could be used for mindfulness intervention for suicidality in Asian older adults. This paper aimed to review recent research relevant to smartphone applications that could be used in providing mindfulness interventions for suicidality to Asian older adults. The inclusion criteria for this review were papers published in peer-reviewed journals from 2008 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…54 Although there has been no published research looking at the effectiveness of using applications such ase Calm and Headspace in OAs, these apps could be a useful tool to address anxiety. 55 Social isolation and quarantine can decrease physical activity and promote sedentary behavior, which is problematic in a population that already spends 60% of awake time engaged in sedentary activities. 56 Sedentary behavior is associated with disability in activities of daily living, development of metabolic syndrome, and an increased risk of all-cause mortality in the elderly.…”
Section: Health and Fitness Apps (Calm Headspace Yoga: Down Dog Anmentioning
confidence: 99%
“…54 Although there has been no published research looking at the effectiveness of using applications such ase Calm and Headspace in OAs, these apps could be a useful tool to address anxiety. 55 Social isolation and quarantine can decrease physical activity and promote sedentary behavior, which is problematic in a population that already spends 60% of awake time engaged in sedentary activities. 56 Sedentary behavior is associated with disability in activities of daily living, development of metabolic syndrome, and an increased risk of all-cause mortality in the elderly.…”
Section: Health and Fitness Apps (Calm Headspace Yoga: Down Dog Anmentioning
confidence: 99%
“…Technology-based mindfulness programs are on the horizon for older adults. Choo et al (2018) reported on the potential use of a smartphone App to deliver mindfulness interventions to older Asian adults at risk for suicide [63]. In another study, Ungar et al (2019) used an online mindfulness program that was greatly beneficial to lonely older adults [64].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this paper is to review and evaluate the evidence base on digital mindfulness trainings in the speci c context of cognitive functions. This aim discriminates the present review from existing ones that addressed traditional mindfulness trainings (Cásedas et al, 2020;Alberto Chiesa et al, 2011), focused on health-related outcomes (Choo et al, 2018), or summarized characteristics of digital mindfulness trainings (Russell et al, 2018). Speci c research questions address (1) the nature of digital mindfulness trainings, (2) the effectiveness of these trainings in improving cognitive functions (attention, memory, and executive functions), in (3) healthy adults, adolescents, and children.…”
Section: Objectivementioning
confidence: 99%